Analysis Of Factors Associated With Dental Caries In Children Aged 6-12 Years Visiting A Private Dental Hospital - BALAJI, KEERTHANA; KUMAR R, PRADEEP; D, PRADEEP (The journal of contemporary issues in business and government, 2021)
Dental caries is the most common oral health disease of school aged children around the world. In the present study we aimed to analyse the factors associated with dental caries among 6 to 12 years old children visiting Private Dental Hospital.This study was designed as a retrospective study, conducted among patients who reported to the University Hospital.Subjects of age group 6-12 years, patient records with complete data were included in this study.Medically compromised patients and patients records with incomplete data were excluded from this study.Data was collected and tabulated in Excel and Data was analysed using IBM SPSS Statistical Analyser(23.0 version).Frequency distribution and descriptive analysis were carried out.The association between the variables was analysed and assessed using Chi-square test.p value less than or equal to 0.05 was considered to be statistically significant.Mean decay value was found to be higher in 6 years old and Mean DMFT value was found to be higher in 9 years old.These mean differences were statistically significant.Increased prevalence of dental caries was most commonly seen in maxillary molars and least in maxillary canines.Prevalence of dental caries was observed to be higher in children with more sugar consumption and irregular oral hygiene practices.Dietary factors and oral Hygiene habits play significant roles in the prevalence of dental caries among school children.